Pelatihan Pemanfaatan Tanaman Obat Untuk Peningkatan SDM Di Desa Banjar Agung Udik, Tanggamus, Lampung - Nida Lidya Susanti; Endah Setyaningrum; Nuning Nurcahyani; Endang Linirin Widiastuti (CV. Multi Kreasi Media, 2024)
Community Service Program aims to provide training on using technology-based medicinal plants to improve human resources and the health of the Banjar Agung Udik village community, Tanggamus, Lampung. This activity will ultimately provide insight, knowledge, abilities, and skills to Banjar Agung Udik village residents in utilizing natural materials in the surrounding environment as health drinks. This work was conducted on Tuesday, August 6, 2024 at 08.00-12.00 WIB with targeted audience are teenagers, PKK members and men in Banjar Agung Udik village. In addition, village officials also attended this activity. The training activity began with preparing plan and dividing the tasks of the service team, preparing the tools and materials needed during the training, and determining the training schedule. The activity ended with socialization and direction on making healthy drinks based on local natural resources. The results of this activity showed that the community was enthusiastic and actively involved in participating in the health drink-making training. With ongoing training, participants are expected to have the knowledge and skills that can be used to improve the quality of health, and even support community economic needs.